2006
DOI: 10.17221/3433-pse
|View full text |Cite
|
Sign up to set email alerts
|

Hot pepper response to interactive effects of salinity and boron

Abstract: An excess of salinity and boron (B) can limit production of hot pepper (Capsicum annuum L.), but little is known about the physiological responses, including antioxidant activities, in response to these excesses. We investigated the physiological responses and defense mechanisms of hot pepper grown under salinity (NaCl) stress at 3 and 6 dS/mand B stress at 15 and 30 mg/kg. Dry weight and the total chlorophyll content decreased with increasing salinity and B levels. The toxic effect of B was greater under sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 34 publications
(29 reference statements)
1
10
0
1
Order By: Relevance
“…Bingham et al (1987) reported that wheat shoot growth was influenced by each stress independently but not by their interaction. Several studies have shown that salt stress may increase B toxicity symptoms and reduce crop yield (Aspaslan and Gunes 2001; Grieve and Poss 2000;Supanjani 2006;Wimmer et al 2003). Conversely, results of other studies suggest that increased salinity may reduce B uptake and mitigate its toxic effects in wheat (Holloway and Alston 1992), chickpeas (Yadav et al 1989), melons (Edelstein et al 2005), and eucalyptus (Grattan et al 1997;Marcar et al 1999).…”
Section: Boronmentioning
confidence: 99%
“…Bingham et al (1987) reported that wheat shoot growth was influenced by each stress independently but not by their interaction. Several studies have shown that salt stress may increase B toxicity symptoms and reduce crop yield (Aspaslan and Gunes 2001; Grieve and Poss 2000;Supanjani 2006;Wimmer et al 2003). Conversely, results of other studies suggest that increased salinity may reduce B uptake and mitigate its toxic effects in wheat (Holloway and Alston 1992), chickpeas (Yadav et al 1989), melons (Edelstein et al 2005), and eucalyptus (Grattan et al 1997;Marcar et al 1999).…”
Section: Boronmentioning
confidence: 99%
“…Many investigations on salinity-nitrogen issue were focused either on nitrogen influence on plant (Ozer et al 2004 andSvoboda andHaberle 2006) or on salinity as limiting plant growth factor (i.e., Burger and Celkova 2003, Orak and Ates 2005and Supanjani and Lee 2006. Fertilization with N may be contributing to soil salinization and increase the negative effects of soil salinity on plant performance during a specific growth stages (Villa-Castorena et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Es importante destacar que cuanto mayor es la relación entre ambos cationes mayor es el daño en los cultivos, debido a la toxicidad por Na + y a la menor absorción de K + . Diferentes estudios demuestran que a pesar de que la fertilización de K + disminuye la relación Na/K, no contrarresta los efectos negativos de la salinidad (Bar-Tal et al, 2001;Supanjani, 2006) Respecto al Ca +2 , en diversas fuentes se indica la importancia de mantener relaciones adecuadas con el Na + , a fin de evitar deficiencias inducidas por competencia de absorción catiónica (Alemán et al, 2009;Turhan et al, 2009). Cuando la concentración de Na + es elevada se presenta mayor incidencia de BER en los cultivos de fruto (De Pascale et al, 2003) y tip burn en los cultivos de hoja (Saure, 2001).…”
Section: Cationes Intercambiables Y Sodicidad (Psiunclassified